Racial and Ethnic Differences in Health Care Utilization Following Severe Acute Brain Injury in the United States. (October 2021) - Jones, Rayleen C.; Creutzfeldt, Claire J.; Cox, Christopher E.; Haines, Krista L.; Hough, Catherine L.; Vavilala, Monica S.; Williamson, Theresa; Hernandez, Adrian; Raghunathan, Karthik; Bartz, Raquel; Fuller, Matt; Krishnamoorthy, Vijay
Objective: To examine racial and ethnic differences in the utilization of 3 interventions (tracheostomy placement, gastrostomy tube placement, and hospice utilization) among patients with severe acute brain injury (SABI). Design: Retrospective cohort study. Setting: Data from the National Inpatient Sample, from 2002 to 2012. Patients: Adult patients with SABI defined as a primary diagnosis of stroke, traumatic brain injury, or post-cardiac arrest who received greater than 96 hours of mechanical ventilation. Exposure: Race/ethnicity, stratified into 5 categories (white, black, Hispanic, Asian, and other). Measurements and Main Results: Data from 86 246 patients were included in the cohort, with a mean (standard deviation) age of 60 (18) years. In multivariable analysis, compared to white patients, black patients had an 20% increased risk of tracheostomy utilization (relative risk [RR]: 1.20, 95% CI: 1.16-1.24, P < .001), Hispanic patients had a 10% increased risk (RR: 1.10, 95% CI: 1.06-1.14, P < .001), Asian patients had an 8% increased risk (RR: 1.08, 95% CI: 1.01-1.16, P = .02), and other race patients had an 10% increased risk (RR: 1.10, 95% CI: 1.04-1.16, P < .001). A similar relationship was observed for gastrostomy utilization. In multivariable analysis, compared to white patients, black patients had a 25% decreased risk of hospice discharge (RR: 0.75, 95% CI: 0.67-0.85, P < .001), Hispanic patients had a 20% decreased risk (RR: 0.80, 95% CI: 0.69-0.94, P < .01), and Asian patients had a 47% decreased risk (RR: 0.53, 95% CI: 0.39-0.73, P < .001). There was no observed relationship between race/ethnicity and in-hospital mortality. Conclusions: Minority race was associated with increased utilization of tracheostomy and gastrostomy, as well as decreased hospice utilization among patients with SABI. Further research is needed to better understand the mechanisms underlying these race-based differences in critical care.